Identification of a Bifunctional Maize C- and O-Glucosyltransferase - Falcone Ferreyra, María Lorena (2013)
Flavonoids accumulate in plant vacuoles usually as O-glycosylated derivatives, but several species can also synthesize flavonoid C-glycosides. Recently, we demonstrated that a flavanone 2-hydroxylase (ZmF2H1, CYP93G5) converts flavanones to the corresponding 2-hydroxy derivatives, which are expected to serve as substrates for C-glycosylation. Here, we isolated a cDNA encoding a UDP-dependent glycosyltransferase (UGT708A6), and its activity was characterized by in vitro and in vivo bioconversion assays. In vitro assays using 2-hydroxyflavanones as substrates and in vivo activity assays in yeast co-expressing ZmF2H1 and UGT708A6 show the formation of the flavones C-glycosides. UGT708A6 can also O-glycosylate flavanones in bioconversion assays in Escherichia coli as well as by in vitro assays with the purified recombinant protein. Thus, UGT708A6 is a bifunctional glycosyltransferase that can produce both C- and O-glycosidated flavonoids, a property not previously described for any other glycosyltransferase.